Four‐Year Behavioral, Health‐Related Quality of Life, and BMI Outcomes from a Cluster Randomized Whole of Systems Trial of Prevention Strategies for Childhood Obesity. Issue 6 (5th May 2021) - Allender, Steven; Orellana, Liliana; Crooks, Nic; Bolton, Kristy A.; Fraser, Penny; Brown, Andrew Dwight; Le, Ha; Lowe, Janette; de la Haye, Kayla; Millar, Lynne; Moodie, Marjorie; Swinburn, Boyd; et al.
Abstract : Objective: This study aimed to test the effectiveness of the Whole of Systems Trial of Prevention Strategies for Childhood Obesity (WHO STOPS Childhood Obesity) for behavioral, health‐related quality of life (HRQoL), and BMI outcomes. Methods: This was a cluster randomized trial of 10 communities randomly allocated (1:1) to start intervention in 2015 (step 1) or in 2019 (after 4 years) in South West Victoria, Australia. Data were collected from participating primary schools in April to June of 2015 (73% school participation rate), 2017 (69%), and 2019 (63%). Student participation rates were 80% in 2015 (1, 792/2, 516 invited), 81% in 2017 (2, 411/2, 963), and 79% in 2019 (2, 177/2, 720). Repeat cross‐sectional analyses of measured height and weight (grades two, four, and six [aged approximately 7 to 12 years]), self‐reported behavior, and HRQoL (grades four and six) were conducted. Results: There was an intervention by time interaction in BMI z scores ( P = 0.031) and obesity/overweight prevalence ( P = 0.006). BMI z score and overweight/obesity prevalence decreased between 2015 and 2017 and increased between 2017 and 2019 in intervention communities. The intervention significantly reduced takeaway food consumption ( P = 0.034) and improved physical ( P = 0.019), psychosocial ( P = 0.026), and global ( P = 0.012) HRQoL. Water consumption increased among girls ( P = 0.033) in the intervention communities, as did energy‐dense, nutrient‐poor snack consumption among boys ( P = 0.006). Conclusions: WHO STOPS had a positive impact on takeaway food intake and HRQoL.